The Spanish National Network “Grupo Castrillo”: 22 Years of Nationwide Neonatal Infection Surveillance - Fernandez Colomer, Belen; Cernada Badia, Maria; Coto Cotallo, Daniel; Lopez Sastre, Jose; Grupo Castrillo Network (American Journal of Perinatology, 2020)
Objective This study aimed to describe the epidemiology of vertically transmitted sepsis (VS) and nosocomial sepsis (NOS) in very low birth weight (VLBW) neonates (birth weight ≤ 1,500 g) over the past 22 years in Spain.Study Design This is a retrospective analysis of prospectively collected VS and NOS in neonates from 1996 to 2018 in the 44 neonatal units integrated in the Spanish Neonatal Network Grupo Castrillo.Results A total of 2,676 episodes of VS were recorded in 2,196,129 live births (LBs; 1.2/1,000 LBs) over the study period (1996–2018). The incidence declined from 2.4 to 1 to 1.2/1,000 LBs (p < 0.0001). Of the 2,676 episodes, 95.7% were early onset (≤72 hours) and 4.3% cases late onset VS. Group B streptococcus (GBS) (33.1%) and E. coli (29.3%) were the most frequently isolated pathogen. The GBS incidence declined significantly from 1.25 to 0.21/1,000 LBs (p < 0.0001). E. coli incidence showed a significant increase trend in VLBW infants (p < 0.05). The global mortality per 1000 LBs decreased from 0.21 to 0.13/1,000. A total of 7,036 episodes of NOS involving 5,493 VLBW infants were registered over 20,935 neonatal admissions (NAs) in the study period (2006–2018). The incidence was 26.2 per 100 NAs. The median postnatal age at onset was 13 days (interquartile range [IQR]: 9–23 days). Around 80% of cases occurred in infants with a central line in place. Gram positive (GP) bacteria accounted for 66.2% with Staphylococcus epidermidis as the most frequently isolated pathogen, gram negative (GN) bacteria entailed 27.4%, and fungi 6.2%. Klebsiella sp. was the most common GN isolated and Candida albicans the most prevalent fungus. The overall mortality was 8.3%.Conclusion The causative pathogen of neonatal sepsis may change over time and between countries, therefore a national surveillance network based on a consensus definition could be essential to provide accurate information.Key Points
Keywords: neonatal sepsis; vertical transmission; nosocomial transmission